Makna Upacara Bau Lolon Pada Masyarakat Desa Puhu Kecamatan Adonara Timur Kabupaten Flores Timur - Rudolof J. Isu; Rocky Paulus Sekoni; Deby Malelak; Yenssy Fanggidae (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study is to describe and explain the meaning contained in the Bau Lolon ceremony for the people of Puhu Village, East Adonara District, East Flores Regency. The benefits of this study are that theoretically the results of this research are useful for (1) developing theoretical concepts as well as procedures and benefits of carrying out the Bau Lolon ceremony for the people of Puhu Village, East Adonara District, East Flores Regency; (2) Can add insight and cultural knowledge related to traditional rituals. While the practical benefits are (1) as input for the East Flores government to keep and maintain the meaning of the Bau Lolon ritual for the people of Puhu Village, East Adonara District, East Flores Regency; (2) as reference material and information in studying culture in the people of Puhu Village, East Adonara District, East Flores Regency; and (3) as an alternative material for local content lessons in schools. The theory used is the hermeneutical theory. The method used in this research is descriptive qualitative method. The results of the study show that the meaning contained in the Bau Lolon ceremony for the people of Puhu Village, East Adonara District, East Flores Regency is as follows: (1) Religious meaning; (2) The meaning of respect for the ancestors; (3) The meaning of application and protection; and (4) cultural meaning.